The Effectiveness of Sistem Informasi Pengelolaan Arsip Surat (SIPAS) for Retrieval of Incoming and Outgoing Letters at Vocational High Schools 8 Semarang - Almira Fury Fabrianne (Diplomatika: Jurnal Kearsipan Terapan, 2021)
Vocational High School 8 Semarang is one of the educational institutions that manually still uses agenda books for managing their letters. Therefore, an innovative filing system was created in the form of a Sistem Informasi Pengelolan Arsip Surat (SIPAS). The purpose of this research  is to find out how effective the application of SIPAS was for retrieval of incoming and outgoing letters at Vocational High School Negeri 8 Semarang. The research method used is descriptive quantitative. The results of the data analysis show that SIPAS obtains 100% accuracy in letters archive retrieval and the retrieval time is only 8 to 10 seconds.